Selecting among land sparing, sharing and Triad in a temperate rainforest depends on biodiversity and timber production targets. Issue 4 (13th March 2023) - Harris, Scott H.; Betts, Matthew G.
Abstract: As demand for wood products increases in step with global population growth, balancing the potentially competing values of biodiversity conservation, carbon storage and timber production is a major challenge. Land sparing involves conserving forest while growing timber in intensively managed areas. On the other hand, land sharing utilizes ecological forestry approaches, but with a larger management footprint due to lower yields. While the sparing‐sharing framework has been widely tested and debated in agricultural settings to balance competing values, such land‐allocation strategies have been rarely studied in forestry. We examined whether a sparing, sharing or Triad strategy best achieves multiple forest objectives simultaneously. In Triad, management units (stands) in forest landscapes are allocated to one of three treatments: reserve (where conservation is the sole objective), intensive (timber production is the sole objective) and ecological (both objectives are combined). To our knowledge, ours is the first Triad study from the temperate zone to quantify direct measures of biodiversity (e.g. species' abundance). Using a commonly utilized forest planning tool parameterized with empirical data, we modelled the capacity of a temperate rainforest to provide multiple ecosystem services (biodiversity, carbon storage, timber production and old‐growth forest structure) over 125 years based on 43 different allocation scenarios. We then quantified trade‐offs between scenarios, taking into account the landscape structure, and determined which strategies most consistently balanced ecosystem services. Sparing strategies were best when the services provided by both old‐growth and early seral (young) forests were prioritized, but at a cost to species associated with mid‐seral stages, which benefitted most from Triad and sharing strategies. Therefore, sparing provides the greatest net benefit, particularly given that old‐growth‐associated species and ecosystem services are currently of the greatest conservation concern. Synthesis and applications . We found that maximizing multiple elements of biodiversity and ecosystem services simultaneously with a single management strategy was elusive. The strategy that maximized each service and species varied greatly by both the service and the level of timber production. Fortunately, a diversity of management options can produce the same wood supply, providing ample decision space for establishing priorities and evaluating trade‐offs. Abstract : We found that maximizing multiple elements of biodiversity and ecosystem services simultaneously with a single management strategy was elusive. The strategy that maximized each service and species varied greatly by both the service and the level of timber production. Fortunately, a diversity of management options can produce the same wood supply, providing ample decision space for establishing priorities and evaluating trade‐offs.